LA MUSICA IN ETÀ ELLENISTICA - Aldo Brancacci (Lexicon Philosophicum)
This paper focuses on two authors, who respectively represent music as a specific discipline and philosophical reflection on music in the Hellenistic Age. The first part of this article is devoted to the Sectio canonis deriving from the 4th and 3rd century BC Pythagorean or Academic tradition, although it is erroneously attributed to Euclid; the second part is about Diogenes of Babylon, a well-known spokesperson of Late Stoicism who was the maxima auctoritas in the musical field in his school. Diogenes’ position cannot be explained without taking into account the harsh criticism by Philodemus of Gadara, the 1st-century Epicurean philosopher who was one of the most important proponents of the theoretical interests and argumentative methods of the philosophical tradition against music.